Ethno-cultural contacts of Tatars with central Asia and their importance for the development of literature (the 16th–19th centuries) - Rezeda R. Abyzova (Историческая этнология, 2017)
The article shows the importance of international ethno-cultural contacts on the example of cross-cultural relations that existed between the Volga region and Central Asia for over several centuries. The basic background of close economic, cultural, and social interactions between these regions is defined. The article identifies the main factors that influenced the entry of cultural, particularly literary monuments, which had been created in the foreign cultural environment, into the territory of the Volga Region.